2015
DOI: 10.1371/journal.pone.0144115
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Patterns of Soil Respiration and Related Soil Biochemical Properties under Nitrogen Addition in Winter Wheat Field

Abstract: Understanding the changes of soil respiration under increasing N fertilizer in cropland ecosystems is crucial to accurately predicting global warming. This study explored seasonal variations of soil respiration and its controlling biochemical properties under a gradient of Nitrogen addition during two consecutive winter wheat growing seasons (2013–2015). N was applied at four different levels: 0, 120, 180 and 240 kg N ha-1 year-1 (denoted as N0, N12, N18 and N24, respectively). Soil respiration exhibited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 59 publications
0
9
1
Order By: Relevance
“…The largest effects observed in this study were attributable to sampling date and depth, which is similar to other studies (Aon and Colaneri, 2001; Deng, 1996; Deng and Tabatabai, 1997; Kaurin et al, 2018; Mariscal‐Sancho et al, 2018). Year‐to‐year (Reardon et al, 2014), seasonal (Aon and Colaneri, 2001; Mariscal‐Sancho et al, 2018; Wuest, 2014, 2015), and even monthly (Liang et al, 2015) variability can be observed for soil measurements as factored by climatic, environmental, and plant‐induced changes to the soil physical and chemical properties. Some of the year‐to‐year variability in this study may be explained both environmentally in terms of soil water, timing of moisture, cumulative growing degree‐days, and the amount of crop biomass returned to the soil.…”
Section: Discussionmentioning
confidence: 99%
“…The largest effects observed in this study were attributable to sampling date and depth, which is similar to other studies (Aon and Colaneri, 2001; Deng, 1996; Deng and Tabatabai, 1997; Kaurin et al, 2018; Mariscal‐Sancho et al, 2018). Year‐to‐year (Reardon et al, 2014), seasonal (Aon and Colaneri, 2001; Mariscal‐Sancho et al, 2018; Wuest, 2014, 2015), and even monthly (Liang et al, 2015) variability can be observed for soil measurements as factored by climatic, environmental, and plant‐induced changes to the soil physical and chemical properties. Some of the year‐to‐year variability in this study may be explained both environmentally in terms of soil water, timing of moisture, cumulative growing degree‐days, and the amount of crop biomass returned to the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that soil microbial activity decreased due to excessive soil moisture [23,40,41]. Liang et al [42] also observed that excessive water noticeably suppressed microbial activity in the semi-arid cropland of China. Because soil moisture was maintained over 0.20 m 3 m −3 in our study, excessive soil moisture might have decreased microbial activity in the first year of this experiment.…”
Section: Effect Of Cultivation Management On the Co 2 Fluxmentioning
confidence: 99%
“…Soil C redistribution and microbial habitat condition were altered under manure and crop residues inputs 78 . Previous studies confirmed that different fertilization managements might affect the soil biological processes, through changing the soil environment, the nutrients and turnover of aggregate, which could directly or indirectly affect C storage [80][81][82] . This study showed that NP made a significant reduction of the microbial biomass ( Fig.…”
Section: Discussionmentioning
confidence: 84%